Safe use of agrochemicals under soil-plant-animal and human system - Kumar, Narendra; Dutta, Asik; Mrunalini, Kancheti; Behera, Biswaranjan; Nath, C P; Praharaj, C S (Indian Farming, 2021)
Application of synthetic agrochemicals remains the principal technique for the control of pests and diseases in conventional agriculture, but it is acknowledged thatagricultural production will be seriously threatened if sustainable techniques are not adopted. Many studies have shown that the intensive use of synthetic chemicals leads to irreversible damage to the structure and ecology of soil and living organisms. In present day intensive agriculture, it is not possible to leave the use of chemicals completely. Hence, integrated approaches like tailing down the synthetic load and substitute the same with botanicals, control/sustained release materials, nano-compounds along with mechanical, agronomical and biological measures should be amalgamated to protect our precious natural resources. Pesticides or fertilisers due to their complex reactions easily gets bio-accumulated and enter into food chain so, our practices should prioritise to reduce the risk of accretion. More field based long term studies should be done on multi location basis to get concrete evidences of pest control. Research institutes and government organisations should come forward and work together for promoting the products and creating awareness in the farming communities.